5y-7+y+27=5y+20-3y

Simple and best practice solution for 5y-7+y+27=5y+20-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-7+y+27=5y+20-3y equation:


Simplifying
5y + -7 + y + 27 = 5y + 20 + -3y

Reorder the terms:
-7 + 27 + 5y + y = 5y + 20 + -3y

Combine like terms: -7 + 27 = 20
20 + 5y + y = 5y + 20 + -3y

Combine like terms: 5y + y = 6y
20 + 6y = 5y + 20 + -3y

Reorder the terms:
20 + 6y = 20 + 5y + -3y

Combine like terms: 5y + -3y = 2y
20 + 6y = 20 + 2y

Add '-20' to each side of the equation.
20 + -20 + 6y = 20 + -20 + 2y

Combine like terms: 20 + -20 = 0
0 + 6y = 20 + -20 + 2y
6y = 20 + -20 + 2y

Combine like terms: 20 + -20 = 0
6y = 0 + 2y
6y = 2y

Solving
6y = 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
6y + -2y = 2y + -2y

Combine like terms: 6y + -2y = 4y
4y = 2y + -2y

Combine like terms: 2y + -2y = 0
4y = 0

Divide each side by '4'.
y = 0

Simplifying
y = 0

See similar equations:

| 7(0)-2(6)=12 | | x^2+y^2+18x+17=0 | | x(x)=16316 | | 190=-8+9x | | 8x-14=-16 | | 7(5x+8)=-x+4 | | 0.10(y-9)+0.12y=0.18y-0.07(10) | | 7(5x+8)=-x+4 | | 8(2x+1)=7x+7 | | 4-9=6+x | | 4-9=6+x | | 4-9=6+x | | x-47=28 | | 4x^3(6)= | | 4=x/2+8 | | 32-4(9-2)=4(T-1) | | -81=-4x+3 | | X+1(4x-2)=2x-1(3x-1) | | 20-3z=7z+8 | | x/10+6=8 | | 2(2x+3)-3=5 | | 4(2x-1)+4=x+25 | | 3.3z-2.3z+0.4=-7.2 | | (4-2i)(6-5i)=0 | | -33=3(4c+5) | | (x+5)2=16x | | x+2(49)=115 | | (5y+2)(3y-1)= | | 3(2x-1)+4=y+25 | | x(x)=1525 | | (x^2)+(18x)+(90)=0 | | 2.5(x-3.6)=x(1.6) |

Equations solver categories